Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5249/jivr.v6i2.318
|View full text |Cite
|
Sign up to set email alerts
|

The impact of environmental factors on traffic accidents in Iran

Abstract: Abstract:Background:Road traffic crashes are the third highest cause of mortality in Iran. The aim of this study was to determine the impact of roadway environmental factors on traffic crash. Methods:This cross-sectional study was conducted in Iran between March 21, 2010 and December 30, 2010. The data on road traffic crashes were obtained from the Traffic Police Department records. These records were classified to control for the main confounders related to the type of crash and roadway environmental factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 17 publications
2
39
1
1
Order By: Relevance
“…In similar studies, blunt abdominal trauma was reported to be more common in men. 1,4,7,9 This is probably due to the outdoor activity of men.…”
Section: Data Collection Tools: Questionnairementioning
confidence: 99%
See 4 more Smart Citations
“…In similar studies, blunt abdominal trauma was reported to be more common in men. 1,4,7,9 This is probably due to the outdoor activity of men.…”
Section: Data Collection Tools: Questionnairementioning
confidence: 99%
“…In similar studies, the majority of patients with blunt abdominal trauma were in the third decade of their lives. 1,4 The blunt abdominal trauma occurred more often in younger ages, probably due to being more active in this range of age. Therefore, we can prevent many cases of blunt abdominal trauma by educating and changing culture in this age group.…”
Section: Data Collection Tools: Questionnairementioning
confidence: 99%
See 3 more Smart Citations